2022
DOI: 10.3390/biology11050797
|View full text |Cite
|
Sign up to set email alerts
|

An Insight Based on Computational Analysis of the Interaction between the Receptor-Binding Domain of the Omicron Variants and Human Angiotensin-Converting Enzyme 2

Abstract: Concerns have been raised about the high number of mutations in the spike protein of the new emergence of the highly transmissible Omicron variant (B.1.1529 lineage) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This variant’s extraordinary ability to evade antibodies would significantly impair the current vaccination program. This present study aimed to computationally analyze the interaction between the receptor-binding domain (RBD) in the spike protein of Omicron variants and human angiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…This aligns with the findings of an experimental investigation through protein binding assay using Microscale thermophoresis (MST), which revealed that the Omicron variant exhibits a five-fold greater affinity compared to the wild type [18]. Furthermore, this is in agreement with other computational studies which suggested that the Omicron variant binds to ACE2 more strongly than the wild type [50][51][52]. BA.2.75 and BA.4.6_N658S were found to be the most and the least stable variants, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…This aligns with the findings of an experimental investigation through protein binding assay using Microscale thermophoresis (MST), which revealed that the Omicron variant exhibits a five-fold greater affinity compared to the wild type [18]. Furthermore, this is in agreement with other computational studies which suggested that the Omicron variant binds to ACE2 more strongly than the wild type [50][51][52]. BA.2.75 and BA.4.6_N658S were found to be the most and the least stable variants, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…The significant number of mutations in the newly emerged, highly transmissible Omicron variants of SARS‐CoV‐2 has aroused concern. The exceptional capacity of the more than 50 mutations overall to avoid antibodies may considerably compromise the existing immunisation effort 1,2 . About 30 of these are mutations in the spike protein 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The exceptional capacity of the more than 50 mutations overall to avoid antibodies may considerably compromise the existing immunisation effort. 1,2 About 30 of these are mutations in the spike protein. 3 The Omicron variant has been shown to improve its transmissibility and ability to evade the immune system, 4 but there are also reports that it reduces hospitalisation rates and causes milder symptoms, such as in vaccinated individuals.…”
mentioning
confidence: 99%
“…In this study, binding affinity analysis allows for determining suitable ligands within the oocyte and sporozoite stage of Plasmodium that could bind to a specific region within FecA (Table 1). With a negative-valued binding affinity, it indicates a thermodynamically favorable ligand-receptor interaction that has a strong affinity binding to the protein, and a stable complex that can induce further signaling cascade [60].…”
Section: Resultsmentioning
confidence: 99%